Urban Climate Resilience and Its Link to Global Sustainability Agendas - Valencia, Sandra C.; Simon, David; Croese, Sylvia; Davison, Amy; Diprose, Kristina; Srinivas, Aishwarya Krishnaswami; Nesprias, Julia; Nordqvist, Joakim; Oloko, Michael; Sharma, Tarun; Buck, Nick Taylor; Versace, Ileana (Academia, 2021)
This chapter examines urban climate resilience. It provides a conceptual introduction, followed by an explanation of how urban areas have been recognized in recent global agendas related to sustainability, climate change, and disaster risk reduction. The chapter provides a picture of the complexity and diversity of urban climate resilience experiences, through seven case study cities on four continents. The sample of cities includes small, medium, and larger cities, both coastal and landlocked, in diverse political, socioeconomic, and geographical contexts. Drawing on comparative research using co-production between academic researchers and local authority counterparts, the detailed case studies illustrate the climate resilience challenges faced by each city, the work in terms of strategies and initiatives they have carried out and are planning to increase their resilience, as well as the geographical and policy contexts in which those strategies are embedded.
Keywords: Climate resilience; Urban resilience; Cities; Vulnerability; Climate adaptation; Climate change; Global environmental change; Agenda 2030; Urban sustainability